Continuous capture scale down model: A comparison of a continuous and a discrete approach. Issue 9 (31st May 2021) - Seidel, Jonathan C.; Göbel, Mathias; Dos Reis Rodrigues, Rui C.; Kaup, Nora M.; Rapp, Johanna; Frauenschuh, Achim; Shultz, Joseph; Cui, Huanchun
Abstract: In continuous pharmaceutical manufacturing, consisting of a perfused batch fermentation and integrated continuous downstream processing, the continuous capture is the linking unit operation. For the development of this unit operation, scale‐down models (SDMs) are crucial, whereas discrete, noncontinuous SDMs are preferred over continuous SDM due to their simplistic nature, reduced material consumption, and shorter operation time. The results presented in this study show the suitability of a discrete SDM approach, compared to a continuous SDM for a continuous protein A purification step. Abstract : The qualification of a scale‐down model for a continuous process is complex and time consuming. With the possibility of using a discrete scale‐down model, these disadvantages could be avoided. This study presents a comparison between a continuous and a discrete scale‐down model for a protein A capture step.